SPECTRUM OF GLOMERULAR DISEASES: AN 11 YEAR RETROSPECTIVE REVIEW IN A TERTIARY CARE HOSPITAL IN PAKISTAN - Naila Asif; Kunwer Naveed Mukhtar (Journal of University Medical & Dental College, 2015)
ABSTRACTBACKGROUND: In this study we report our experience with renal biopsy and histopathological pattern of renal disease in a tertiary care hospital in Pakistan over an 11 year period. PATIENTS AND METHOD: All the kidney biopsies performed in our unit from Jan 2001 to Dec 2011 were retrospectively reviewed but only glomerular diseases were analyzed. We recorded the following data for each patient: name, age, sex, indications for renal biopsy, histopathological diagnosis and lab investigations such as Serum Creatinine 24 hour urinary protein, urine microscopy, virology (HbsAg, Anti HCV) and serology (anti-ds DNA, ANA, C3, C4, C-ANCA and pANCA) when indicated. Analysis included Light Microscopy (LM) and immunoﬂourescene (IF). For LM, three sections were stained with H and E.Pas and special stains were used when warranted. IF study was done using polyclonal antisera against human IgG, IgM, IgA, C3 and Cq. The renal biopsies were performed by a trained Nephrologist. Biopsies were evaluated by light microscopy and IF and also special stains were warranted.RESULTS: A total of 310 consecutive percutaneous renal biopsies of native kidneys showed glomerular disease in 248 cases. A total of thirteen specimens were unsatisfactory. There were 125 males (50.4%) and 123 females (49.6%). Age distribution showed a total no. of 29 (11.69%) of paediatric cases, 200 (80.6%) adult cases and 19 (7.6 %) elderly cases. The most common clinical indication for renal biopsy was nephrotic syndrome (n=83 33.5%) which was followed by unexplained renal failure (n=67 27.0%). Of the total biopsies included 184 (74%.19%) had *primary glomerular disease and 64 (34.78%) had secondary glomerular diseases. The most frequently found primary glomerular leison was membranous nephropathy (27.7%) when all age groups were studied together. Membranous nephropathy was also the commonest primary glomerular pathology amongst both the adult group (23%) as well as the elderly group (21%) Lupus nephritis (60%) ranked ﬁrst amongst the secondary glomerular lesions. It was followed by amyloidosis which was found in 26% of the secondary cases. The most common leison according to WHO classiﬁcation was Class V Lupus Nephritis (48.7%).CONCLUSION: Membranous Nephropathy was the most frequently found lesions in Primary glomerular diseases. Lupus Nephritis was the most common secondary glomerular disease